(untitled) (Iranian Journal of Kidney Diseases, 2013)
Introduction. Nitric oxide (NO) is one of the endothelium-dependent relaxing factors released by the vascular endothelium. It is decreased in chronic kidney disease. It was found that higher levels of circulating proinflammatory cytokines such as interleukin-1β (IL-1β), tumor necrosis factor-α (TNF-α), IL-6, and IL-13 are associated with mortality. The aim of our study was to evaluate the disturbance in NO in chronic kideny failure and its relationship with hypertension and inflammatory and nutritional parameters, as indirect indexes of uremic oxidative stress. Materials and Methods. This study included 31 children consisting of 23 children, aged from 4 to 18 years old, with ESRD, on regular hemodialysis, and 8 children admitted to hospital for other diseases (control group). Predialysis blood samples were tested for IL-1β, TNF-α, and NO, and were compared with the control group. Results. Serum levels of TNF-α and IL-1β were significantly higher in children on hemodialysis as compared to the control group (TNF-α, 104.54 ± 17.31 pg/mL versus 48.19 ± 6.28 pg/mL, P = .005; IL-1β, 5.35 ± 0.75 pg/mL versus 2.13 ± 0.61 pg/mL, P = .02; respectively). However, the levels of NO, albeit higher in this group had no significant difference with the controls. Conclusions. The levels of cytokines are high in pediatric patients on hemodialysis, which reflects a state of oxidative stress.